Engineering the TiO2–Graphene Interface to Enhance Photocatalytic H2 Production. Issue 2 (9th December 2013) - Liu, Lichen; Liu, Zhe; Liu, Annai; Gu, Xianrui; Ge, Chengyan; Gao, Fei; Dong, Lin
Abstract In this work, TiO2–graphene nanocomposites are synthesized with tunable TiO2 crystal facets (100, 101, and 001 facets) through an anion‐assisted method. These three TiO2–graphene nanocomposites have similar particle sizes and surface areas; the only difference between them is the crystal facet exposed in TiO2 nanocrystals. UV/Vis spectra show that band structures of TiO2 nanocrystals and TiO2–graphene nanocomposites are dependent on the crystal facets. Time‐resolved photoluminescence spectra suggest that the charge‐transfer rate between 100 facets and graphene is approximately 1.4 times of that between 001 facets and graphene. Photoelectrochemical measurements also confirm that the charge‐separation efficiency between TiO2 and graphene is greatly dependent on the crystal facets. X‐ray photoelectron spectroscopy reveals that TiC bonds are formed between 100 facets and graphene, while 101 facets and 001 facets are connected with graphene mainly through TiOC bonds. With TiC bonds between TiO2 and graphene, TiO2‐100‐G shows the fastest charge‐transfer rate, leading to higher activity in photocatalytic H2 production from methanol solution. TiO2‐101‐G with more reductive electrons and medium interfacial charge‐transfer rate also shows good H2 evolution rate. As a result of its disadvantageous electronic structure and interfacial connections, TiO2‐001‐G shows the lowest H2 evolution rate. These results suggest that engineering the structures of the TiO2–graphene interface can be an effective strategy to achieve excellent photocatalytic performances.